An efficient anoxic/aerobic/aerobic/anoxic process for domestic sewage treatment: From feasibility to application - Wang, Yao; Liang, Baorui; Kang, Fei; Wang, Youzhao; Zhao, Chaoyue; Lyu, Zhenning; Zhu, Tong; Zhang, Zhijun (Frontiers in Microbiology, 2022)
In this paper, the anoxic/aerobic/aerobic/anoxic (AOOA) process was proposed using fixed biofilms in a continuous plug-flow multi-chamber reactor, and no sludge reflux operation was performed during the 190 days of operation. The reactor volume ratio of 1.5:2:1.5:1 (A/O/O/A) with the dissolved oxygen (DO) concentration of 2 mg L−1 in the aerobic zone was the optimal condition for reactor operation. According to the results obtained from the treatment of real domestic sewage, when the hydraulic retention time (HRT) was 6 h, the effluent of the reactor could meet the discharge standard even in cold conditions (13 °C). Specifically, the elemental-sulfur-based autotrophic denitrification (ESAD) process contributed the most to the removal of total inorganic nitrogen (TIN) in the reactor. In addition, the use of vibration method was helpful in removing excess sludge from the biofilms of the reactor. Overall, the AOOA process is an efficient and convenient method for treating domestic sewage.